1.6 Tbps High Speed Long Reach DWDM System by incorporating Modified Duobinary Modulation Scheme (International Journal of Current Engineering and Technology, 2014)
This work is focused to investigate the duobinary modulation scheme in high speed DWDM systems. In this work, 40 channels having capacity 40 Gbps each are multiplexed with channel spacing of 50 GHz to realize 1.6 Tbps as total transmission over optical span of 1800 Km by incorporating pre and post dispersion compensation techniques. The non linear effects are limiting factors in narrow channel spaced system and in order to reduce their effects duo binary format is used and attenuation in the fiber is minimized by EDFA. Moreover, the role of laser line-width is also investigated to minimize the non linearity and Four wave mixing effect.
Keywords: DWDM; Laser Line-width; Duo binary Modulation scheme; Pre and Post compensation techniques